Peningkatan Literasi Demam Berdarah Dengue di Kelurahan Sendangmulyo - Puspita Anggraini, Fitria Dewi; Aprianti, Aprianti; Mubarokah, Kismi; Wulandari, Respati (Fakultas Pertania Universitas Muara Bungo, 2023)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the Dengue virus and transmitted by the Aedes aegypti or Aedes albopictus mosquito. Sendangmulyo sub-district is the area with the highest number of dengue fever cases among the sub-districts in the Kedungmundu Health Center working area with the majority of residents' neighborhoods being residential complexes. Effor to control dengue hemorrhagic fever cases need to be increased by involving community participation. The problems faced by the community are the inconsistency of community knowledge and actions in efforts to eradicate mosquito nests in daily life, as well as the low level of public awareness in implementing habits to prevent cases of dengue hemorrhagic fever. The mentoring activities carried out were providing education regarding dengue hemorrhagic fever literacy and its prevention, followed by brainstorming regarding the root causes of the dengue problem in the Sendangmulyo area by producing a Follow-up Plan for implementing regional-based case reduction. Statistically, the pretest-posttest score difference test value for the knowledge, attitude and literacy variables respectively is 2.444 (p=0.015 <0.05); 2.142 (p=0.032 < 0.05) and 1.222 p=0.222 > 0.05). There is a significant difference in the mean pretest and posttest scores on the measurement of knowledge and attitude variables. The follow-up plan agreed upon by residents is the PKK Grebeg Jentik Movement, inspection of larvae in the field using a filter dipper, empty houses that have not been occupied for a long time must still be inspected with permission from the relevant RT, and provision of fishization for residents who have been inspected three times in a row and find larvae.